Thermal conductivity of sedimentary rocks in the Sichuan basin, Southwest China - Boning Tang (Energy Exploration & Exploitation, 2019)
The optical scanning method was adopted to measure the thermal conductivities of 418 drill-core samples from 30 boreholes in Sichuan basin. All the measured thermal conductivities mainly range from 2.00 to 4.00 W/m K with a mean of 2.85 W/m K. For clastic rocks, the mean thermal conductivities of sandstone, mudstone, and shale are 3.06 ± 0.73, 2.57 ± 0.42, and 2.48 ± 0.33 W/m K, respectively; for carbonate rocks, the mean thermal conductivities of limestone and dolomite are 2.53 ± 0.44 and 3.55 ± 0.71 W/m K, respectively; for gypsum rocks, the mean thermal conductivity is 3.60 ± 0.64 W/m K. The thermal conductivities of sandstone and mudstone increase with burial depth and stratigraphic age, but this trend is not obvious for limestone and dolomite. Compared with other basins, the thermal conductivities of sandstone and mudstone in Sichuan basin are distinctly higher, while the thermal conductivities of limestone are close to Tarim basin. The content of mineral composition such as quartz is the principal factor that results in thermal conductivity of rocks differing from normal value. In situ thermal conductivity of sandstones was corrected with the consideration of water saturation. Finally, a thermal conductivity column of sedimentary formation of the Sichuan basin was given out, which can provide thermal conductivity references for the research of deep geothermal field and lithospheric thermal structure in the basin.